Biodegradable plastic product reinforcement material and preparation method thereof
By using clad flame retardant polymer modified polylactic acid and dandelion-like flame retardant in biodegradable plastic products, the shortcomings of existing materials in mechanical properties and flame retardant properties are solved, and the triple improvement of the material is achieved: flame retardant properties, mechanical properties and degradability.
Patent Information
- Application Number
- CN202410773981.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The existing biodegradable plastic product reinforced materials have shortcomings in terms of mechanical properties and flame retardant properties, and it is difficult to meet the more demanding environmental requirements.
The encapsulated flame retardant polymer is used to modify polylactic acid and dandelion-like flame retardant. The encapsulated flame retardant polymer is formed by coating chitosan/alginate on the surface of the ammonium polyphosphate particles, and combined with spherical magnesium aluminum hydroxide flame retardant and melamine phosphate nanowires to form a reinforcement material with excellent flame retardant and mechanical properties.
It significantly improves the flame retardant properties and mechanical properties of biodegradable plastic products, improves the residual weight ratio after combustion and the maximum thermal weight loss rate, enhances the tensile strength, wear resistance and structural stability of the material, and also has excellent degradability and environmental protection properties.
Smart Images

Figure CN118580655B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of degradable materials, and in particular to a biodegradable plastic product reinforcing material and a preparation method thereof. Background Art
[0002] As the global plastic pollution problem continues to intensify, people's demand for environmentally friendly plastics is becoming more and more urgent. Traditional plastic products take hundreds of years to decompose, causing serious pollution and damage to the natural environment. In order to solve this problem, biodegradable plastic products came into being. However, biodegradable plastics are currently relatively weak in strength and durability, which limits their ability to be widely used. In order to improve the performance of biodegradable plastics, researchers have begun to focus on reinforcing materials for biodegradable plastic products. By adding reinforcing materials, such as cellulose and starch, the strength and durability of biodegradable plastics can be significantly improved, enabling them to function in more usage environments and conditions and extend their service life. In addition, the application of reinforcing materials can also reduce the use of plastic products and reduce the pollution of plastic waste to the environment. The research and development and application of reinforcing materials for biodegradable plastic products will make important contributions to solving the problem of plastic pollution, protecting the environment, and promoting sustainable development. By improving the performance and durability of plastic products, reinforcing materials are expected to become a key driving force for the plastic industry to develop in a more environmentally friendly and sustainable direction.
[0003] At present, the development of biodegradable plastic product reinforcement materials has achieved remarkable results, but there are still some shortcomings. (1) The mechanical properties of biodegradable plastic product reinforcement materials need to be further enhanced to meet more stringent use environment requirements. For example, the Chinese patent with publication number CN116948266A discloses a biodegradable plastic with starch and diammonium hydrogen phosphate as the theme, but there is no targeted design reinforcement component in the components, so the mechanical properties are still limited. At the same time, there is no flame retardant effective ingredient in the patent, so the flame retardant performance is poor. (2) The flame retardant performance of biodegradable plastic product reinforcement materials needs to be further enhanced. For example, the Chinese patent with publication number CN117844210A discloses an inorganic flame retardant filler composed of aluminum oxide, aluminum hydroxide, nano silicon oxide, and calcium aluminum silicate. Inorganic flame retardants are usually suitable for materials in some high temperature environments. For materials in low temperature or special environments, they may not provide good flame retardant effects. In addition, inorganic flame retardant fillers have limited contribution to the mechanical properties of biodegradable plastic products. Therefore, biodegradable plastics currently still face many challenges in terms of mechanical properties and flame retardant properties. In order to fill this technological gap, it is necessary to develop a new type of biodegradable plastic with excellent mechanical properties and flame retardant properties to meet the needs of high-performance biodegradable plastics. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a biodegradable plastic product reinforcement material and a preparation method thereof, so as to solve the problem that the current coating has insufficient mechanical properties and flame retardant properties.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The biodegradable plastic product reinforcement material comprises the following components, measured by weight: 45-80 parts of shell flame-retardant polymer modified polylactic acid, 80-120 parts of dandelion-shaped flame retardant, 20-30 parts of starch, 2-4 parts of plasticizer, 3-7 parts of microcrystalline cellulose, 20-35 parts of polyhydroxybutyrate, 1-3 parts of antioxidant, and 3-7 parts of dispersant.
[0009] Furthermore, the preparation method of the shelled flame-retardant polymer modified polylactic acid is as follows: by weight: 60 parts of polylactic acid and 3 to 9 parts of shelled flame-retardant polymer are dried under vacuum conditions at 70 to 90° C. for 8 to 16 hours to remove moisture, and mixed evenly by a melt mixing processing method. The temperature of the melt mixing processing method is 140 to 190° C., the rotation speed is 45 to 65 rpm, and the mixing time is 8 to 15 minutes to obtain the shelled flame-retardant polymer modified polylactic acid.
[0010] Furthermore, the preparation method of the shelled flame-retardant polymer is as follows: by weight, 15 to 28 parts of ammonium polyphosphate are dissolved in 350 to 450 parts of deionized water, and then 1 to 4 parts of chitosan are dissolved in 30 to 50 parts of 10% acetic acid aqueous solution to form a chitosan solution for standby use, and 1 to 3 parts of alginate are dissolved in 30 to 40 parts of 1% ammonia aqueous solution to form an alginate solution. Then, the chitosan solution is added dropwise to the alginate solution and stirred for 5 to 10 minutes to generate the alginate solution, and then the shelled flame-retardant polymer is obtained after centrifugation, washing, and drying.
[0011] The present invention forms a shelled flame-retardant polymer by coating the surface of ammonium polyphosphate particles with chitosan / alginate, which has the following advantages over traditional ammonium polyphosphate. First, in terms of flame retardancy, the shell structure can significantly improve the flame retardant effect. During the combustion process, the chitosan and alginate coating layers can form a dense carbonized layer at high temperature, effectively blocking the exchange of combustible gas and oxygen, thereby significantly inhibiting the spread of flames. This unique flame retardant mechanism significantly improves the flame retardancy, which is specifically manifested in the increase in the residual weight ratio after combustion and the significant reduction in the maximum thermal weight loss rate. Therefore, the shelled flame retardant polymer with the shell structure shows obvious advantages in flame retardancy. Secondly, in terms of mechanical properties, the shelled flame retardant polymer with the shell structure also has significant advantages. Since the coating layer is rich in polyhydroxy structures, these hydroxyls can form a strong interfacial interaction force with the polylactic acid matrix, thereby enhancing the overall mechanical properties of the polymer. This enhancement not only improves the strength of the polymer, but also improves its toughness and impact resistance. More importantly, the shelled flame retardant polymer of the present invention also has excellent degradability. Chitosan and alginate, as natural polymer materials, have good biocompatibility and degradability. Under specific environmental conditions, these materials can gradually decompose into harmless substances, thereby reducing pollution to the environment. At the same time, the polylactic acid matrix in the shelled flame-retardant polymer is also degradable, further enhancing the environmental performance of the overall material. In summary, the present invention successfully achieves a triple improvement in flame retardancy, mechanical properties and degradability by constructing a shelled flame-retardant polymer with a shell structure. Compared with traditional ammonium polyphosphate, the shelled flame-retardant polymer has shown significant advantages in flame retardant effect, mechanical properties and environmental performance, and has broad application prospects, especially in the field of biodegradable plastics.
[0012] Furthermore, the dandelion-shaped flame retardant is composed of a spherical magnesium aluminum hydroxide flame retardant and melamine phosphate nanowires distributed in a scattered manner on its outer layer.
[0013] Furthermore, the average diameter of the spherical magnesium aluminum hydroxide flame retardant is 2 to 6 μm, and the average diameter of the melamine phosphate nanowire is 40 to 90 nm, and the length is 500 to 1500 nm.
[0014] Furthermore, the mass ratio of the spherical magnesium aluminum hydroxide flame retardant to the melamine phosphate nanowire is (10-25):1.
[0015] Furthermore, the preparation method of the dandelion-shaped flame retardant is as follows: by weight, 15 to 25 parts of melamine are dissolved in 200 to 350 parts of dimethylformamide to form a solution A for standby use, and then 15 to 25 parts of polyphosphoric acid are dissolved in 100 to 150 parts of polyphosphoric acid in the same way to form a solution B, and then the solution A is completely dripped into the solution B in 3 to 5 hours in the form of dripping, and after the dripping is completed, 30 to 65 parts of spherical magnesium aluminum hydroxide flame retardant is added, heated to 100 to 120° C., stirred for reaction for 6 to 12 hours, melamine phosphate nanowires are uniformly grown on the surface of the spherical hydroxide inorganic flame retardant, and then the product is filtered and washed three times with deionized water, and then the product is dried at 60 to 80° C. for 20 to 40 hours to obtain the dandelion-shaped flame retardant.
[0016] Furthermore, the mass ratio of melamine to polyphosphoric acid is 1:1.
[0017] Furthermore, the preparation method of the spherical magnesium aluminum hydroxide flame retardant is as follows: by weight, 24 to 46 parts of Mg(NO3)2·6H2O and 12 to 23 parts of Al(NO3)3·9H2O are dissolved in 100 parts of deionized water to form a magnesium aluminum salt solution for use. A C alkaline solution is obtained by dissolving 10 to 15 parts of Na2CO3 and 12 to 20 parts of NaOH in 150 parts of deionized water. The magnesium aluminum salt solution is vigorously stirred, and the pH of the magnesium aluminum salt solution is maintained at 8 to 9 with the C alkaline solution during the stirring process. A hydroxide precipitate is formed during the stirring process, and then filtered and washed with deionized water to neutrality, and then vacuum dried to obtain the spherical magnesium aluminum hydroxide flame retardant.
[0018] Furthermore, the mass ratio of Mg(NO3)2·6H2O to Al(NO3)3·9H2O is 2:1.
[0019] The present invention designs a new type of dandelion-shaped flame retardant, which can significantly improve the mechanical properties and flame retardant properties of biodegradable plastic products when used as a reinforcing material for biodegradable plastic products. In terms of mechanical properties, the spherical magnesium aluminum hydroxide flame retardant in the dandelion-shaped flame retardant provides good mechanical support and reinforcing effect for biodegradable plastic products. This structure can not only improve the tensile strength and wear resistance of the material, but also increase the structural stability and durability of the product. In addition, the melamine phosphate nanowires distributed in a scattered manner on the outer layer further enhance the mechanical properties of the product, making it more durable. In terms of flame retardant properties, the spherical magnesium aluminum hydroxide flame retardant effectively suppresses the spread of flames by virtue of its unique layered structure and good flame retardant properties, and significantly improves the flame retardant properties of biodegradable plastic products. At the same time, the melamine phosphate nanowires distributed in a scattered manner on the outer layer further enhance the flame retardant effect. These nanowires can form a dense protective layer on the surface of the material, effectively isolating oxygen and heat, thereby extending the burning time of the material and further improving the flame retardant properties. The combination of inorganic magnesium aluminum hydroxide and organic melamine phosphate flame retardant forms a synergistic effect, further enhancing the overall flame retardant effect. In addition to its advantages in mechanical properties and flame retardant properties, this dandelion-shaped flame retardant is also environmentally friendly and degradable. Traditional flame retardants usually contain substances such as organic bromine compounds that are harmful to the environment and health, while dandelion-shaped flame retardants use inorganic magnesium aluminum hydroxide and organic melamine phosphate as flame retardants, do not contain harmful substances, and are environmentally friendly. In short, through structural design and material selection, dandelion-shaped flame retardants not only have advantages in mechanical properties and flame retardant properties, but also have the characteristics of environmental protection and degradability, providing a new solution for reducing negative impacts on the environment and promoting sustainable development.
[0020] Furthermore, the plasticizer is hydrogenated castor oil, n-butyl stearate or epoxidized soybean oil.
[0021] Furthermore, the antioxidant is lycopene or sesamol.
[0022] Furthermore, the dispersant is polyvinyl alcohol or sodium carboxymethyl cellulose.
[0023] The present invention also provides a method for preparing a biodegradable plastic product reinforcement material:
[0024] S1. melt-blending the shell flame-retardant polymer modified polylactic acid, dandelion-shaped flame retardant, dispersant and plasticizer at a heating temperature of 150 to 180° C. for 2 to 3 hours.
[0025] S2. Then continue to add starch, microcrystalline cellulose, antioxidant and polyhydroxybutyrate and heat to dissolve at 100-140°C. The heating and dissolving time is 20-30 minutes and the stirring speed is 100-140 rap.
[0026] S3. The molten mixture mixed in step S2 is introduced into an extrusion film blowing machine, and hot melt extrusion blow molding is performed at the same time to obtain a biodegradable plastic product reinforcement material.
[0027] (3) Beneficial technical effects
[0028] The present invention uses chitosan / alginate to coat ammonium polyphosphate particles multiple times, and successfully prepares a new type of shell-coated flame-retardant polymer with a unique core-shell structure. Compared with traditional ammonium polyphosphate, the shell-coated flame-retardant polymer of the present invention shows significant advantages in flame retardancy and mechanical properties. Its unique core-shell structure can form a dense carbonized layer during combustion, effectively blocking the contact between oxygen and combustibles, and significantly improving the flame retardant performance, which is specifically reflected in the substantial increase in residual weight after combustion and the significant reduction in the maximum thermal weight loss rate. At the same time, the strong interfacial interaction formed between the rich polyhydroxy structure in the coating layer and the polylactic acid matrix significantly enhances the overall mechanical properties of the polymer. In addition, the chitosan and alginate used in the present invention are both biodegradable natural polymer materials, which can be decomposed by microorganisms in the natural environment and eventually converted into harmless substances, showing excellent environmental performance. The biodegradable plastic products in the dandelion-shaped flame retardant also have the characteristics of environmental protection and degradability, providing strong support for the application of environmentally friendly materials. It is particularly worth mentioning that the new dandelion-shaped flame retardant designed by the present invention has a significant effect in improving the mechanical properties and flame retardant properties of biodegradable plastic products. The spherical magnesium aluminum hydroxide not only provides excellent mechanical support and wear resistance, but also significantly enhances the structural stability and durability of the product. At the same time, the outer layer of scattered melamine phosphate nanowires not only further strengthens the mechanical properties of the product, but also forms a dense protective layer, effectively isolates oxygen and heat, and significantly prolongs the burning time, thereby significantly improving the flame retardant properties. The synergistic effect between inorganic magnesium aluminum hydroxide and organic melamine phosphate flame retardant further improves the overall flame retardant properties. In addition, by carefully optimizing the ratio of starch, plasticizer, microcrystalline cellulose, polyhydroxybutyrate, antioxidant and dispersant, the present invention effectively improves the mechanical properties, processability, stability and dispersibility of the material, provides an ideal material choice for the production of high-performance biodegradable plastics, and helps to promote the realization of environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the infrared Fourier transform FTIR spectrum of the shelled flame-retardant polymer modified polylactic acid prepared in Example 1 of the present invention.
[0030] Figure 2 This is a scanning electron microscope (SEM) morphology image of the spherical magnesium aluminum hydroxide prepared in Example 1 of the present invention.
[0031] Figure 3 This is a scanning electron microscope (SEM) morphology image of the dandelion-shaped flame retardant prepared in Example 1 of the present invention.
[0032] Figure 4 This is the XRD phase analysis diagram of the spherical magnesium aluminum hydroxide prepared in Example 1 of the present invention.
[0033] Figure 5 This is the XRD phase analysis diagram of the dandelion-shaped flame retardant prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0035] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0036] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0037]
[0038]
[0039] Example 1
[0040] The biodegradable plastic product reinforcement material comprises the following components, measured by weight: 45 parts of shell flame retardant polymer modified polylactic acid, 80 parts of dandelion-shaped flame retardant, 20 parts of starch, 2 parts of plasticizer, 3 parts of microcrystalline cellulose, 20 parts of polyhydroxybutyrate, 1 part of antioxidant, and 3 parts of dispersant.
[0041] The preparation method of the above-mentioned shelled flame-retardant polymer modified polylactic acid is as follows: by weight: 60 parts of polylactic acid and 3 parts of shelled flame-retardant polymer are dried under vacuum conditions at 70°C for 8 hours to remove moisture, and mixed evenly by a melt mixing processing method. The temperature of the melt mixing processing method is 140°C, the rotation speed is 45rpm, and the mixing time is 8min to obtain the shelled flame-retardant polymer modified polylactic acid.
[0042] The preparation method of the shelled flame-retardant polymer is as follows: by weight, 15 parts of ammonium polyphosphate are dissolved in 350 parts of deionized water, and then 1 part of chitosan is dissolved in 30 parts of 10% by weight acetic acid aqueous solution to form a chitosan solution for use, and 1 part of alginate is dissolved in 30 parts of 1% by weight ammonia aqueous solution to form an alginate solution. Then, the chitosan solution is added dropwise to the alginate solution and stirred for 5 minutes to generate the alginate solution, and then the shelled flame-retardant polymer is obtained after centrifugation, washing, and drying.
[0043] The dandelion-shaped flame retardant is composed of a spherical magnesium aluminum hydroxide flame retardant and melamine phosphate nanowires distributed in a scattered manner on its outer layer.
[0044] The average diameter of the spherical magnesium aluminum hydroxide flame retardant is 2 μm, and the average diameter of the melamine phosphate nanowire is 40 nm and the length is 500 nm.
[0045] The mass ratio of the spherical magnesium aluminum hydroxide flame retardant to the melamine phosphate nanowire is 10:1.
[0046] The preparation method of the dandelion-shaped flame retardant is as follows: by weight, 15 parts of melamine are dissolved in 200 parts of dimethylformamide to form a solution A for standby use, and then 15 parts of polyphosphoric acid are dissolved in 100 parts of polyphosphoric acid in the same way to form a solution B, and then the solution A is completely dripped into the solution B in 3 hours, and after the dripping is completed, 30 parts of spherical magnesium aluminum hydroxide flame retardant are added, heated to 100°C, stirred for reaction for 6 hours, and melamine phosphate nanowires are uniformly grown on the surface of the spherical hydroxide inorganic flame retardant, and then the product is filtered and washed three times with deionized water, and then the product is dried at 60°C for 20 hours to obtain the dandelion-shaped flame retardant.
[0047] The preparation method of the spherical magnesium aluminum hydroxide flame retardant is as follows: by weight, 24 parts of Mg(NO3)2·6H2O and 12 parts of Al(NO3)3·9H2O are dissolved in 100 parts of deionized water to form a magnesium aluminum salt solution for use. A C alkaline solution is obtained by dissolving 10 parts of Na2CO3 and 12 parts of NaOH in 150 parts of deionized water. The magnesium aluminum salt solution is vigorously stirred, and the pH of the magnesium aluminum salt solution is maintained at 8 with the C alkaline solution during the stirring process. A hydroxide precipitate is formed during the stirring process, and then filtered and washed with deionized water to neutrality, and then vacuum dried to obtain a spherical magnesium aluminum hydroxide flame retardant.
[0048] The plasticizer mentioned above is hydrogenated castor oil.
[0049] The above-mentioned antioxidant is lycopene.
[0050] The above-mentioned dispersant is polyvinyl alcohol.
[0051] The present invention also provides a method for preparing a biodegradable plastic product reinforcement material:
[0052] S1. melt-blending the shell flame-retardant polymer modified polylactic acid, dandelion-shaped flame retardant, dispersant and plasticizer at a heating temperature of 150° C. for 2 h.
[0053] S2. Then continue to add starch, microcrystalline cellulose, antioxidants and polyhydroxybutyrate and heat to dissolve at 100°C. The heating and dissolving time is 20 minutes and the stirring speed is 100 rap.
[0054] S3. The molten mixture mixed in step S2 is introduced into an extrusion film blowing machine, and hot melt extrusion blow molding is performed at the same time to obtain a biodegradable plastic product reinforcement material.
[0055] Example 2
[0056] The biodegradable plastic product reinforcement material comprises the following components, measured by weight: 55 parts of shell flame retardant polymer modified polylactic acid, 90 parts of dandelion-shaped flame retardant, 22 parts of starch, 3 parts of plasticizer, 4 parts of microcrystalline cellulose, 22 parts of polyhydroxybutyrate, 2 parts of antioxidant, and 4 parts of dispersant.
[0057] The preparation method of the above-mentioned shelled flame-retardant polymer modified polylactic acid is as follows: by weight: 60 parts of polylactic acid and 4 parts of shelled flame-retardant polymer are dried under vacuum conditions at 80°C for 10 hours to remove moisture, and mixed evenly by a melt mixing processing method. The temperature of the melt mixing processing method is 150°C, the rotation speed is 50rpm, and the mixing time is 9 minutes to obtain the shelled flame-retardant polymer modified polylactic acid.
[0058] The preparation method of the shelled flame-retardant polymer is as follows: by weight, 18 parts of ammonium polyphosphate are dissolved in 380 parts of deionized water, and then 2 parts of chitosan are dissolved in 35 parts of 10% acetic acid aqueous solution to form a chitosan solution for use, and 2 parts of alginate are dissolved in 33 parts of 1% ammonia aqueous solution to form an alginate solution. Then, the chitosan solution is added dropwise to the alginate solution and stirred for 6 minutes to generate the alginate solution, and then the shelled flame-retardant polymer is obtained after centrifugation, washing, and drying.
[0059] The dandelion-shaped flame retardant is composed of a spherical magnesium aluminum hydroxide flame retardant and melamine phosphate nanowires distributed in a scattered manner on its outer layer.
[0060] The average diameter of the spherical magnesium aluminum hydroxide flame retardant is 3 μm, and the average diameter of the melamine phosphate nanowire is 50 nm and the length is 800 nm.
[0061] The mass ratio of the spherical magnesium aluminum hydroxide flame retardant to the melamine phosphate nanowire is 14:1.
[0062] The preparation method of the dandelion-shaped flame retardant is as follows: by weight, 20 parts of melamine are dissolved in 250 parts of dimethylformamide to form a solution A for standby use, and then 20 parts of polyphosphoric acid are dissolved in 120 parts of polyphosphoric acid in the same way to form a solution B, and then the solution A is dripped into the solution B completely over 4 hours, and after the dripping is completed, 35 parts of spherical magnesium aluminum hydroxide flame retardant are added, heated to 110°C, stirred for reaction for 8 hours, and melamine phosphate nanowires are uniformly grown on the surface of the spherical hydroxide inorganic flame retardant, and then the product is filtered and washed three times with deionized water, and then the product is dried at 65°C for 24 hours to obtain a dandelion-shaped flame retardant.
[0063] The preparation method of the spherical magnesium aluminum hydroxide flame retardant is as follows: by weight, 28 parts of Mg(NO3)2·6H2O and 14 parts of Al(NO3)3·9H2O are dissolved in 100 parts of deionized water to form a magnesium aluminum salt solution for use. C alkaline solution is obtained by dissolving 11 parts of Na2CO3 and 14 parts of NaOH in 150 parts of deionized water. The magnesium aluminum salt solution is vigorously stirred, and the pH of the magnesium aluminum salt solution is maintained at 8 with C alkaline solution during stirring. A hydroxide precipitate is formed during stirring, and then filtered and washed with deionized water to neutrality, and then vacuum dried to obtain a spherical magnesium aluminum hydroxide flame retardant.
[0064] The plasticizer mentioned above is n-butyl stearate.
[0065] The antioxidant mentioned above is sesamol.
[0066] The above-mentioned dispersant is sodium carboxymethyl cellulose.
[0067] The present invention also provides a method for preparing a biodegradable plastic product reinforcement material:
[0068] S1. melt-blending the shell flame-retardant polymer modified polylactic acid, dandelion-shaped flame retardant, dispersant and plasticizer at a heating temperature of 160° C. for 2 h.
[0069] S2. Then continue to add starch, microcrystalline cellulose, antioxidants and polyhydroxybutyrate and heat to dissolve at 110°C. The heating and dissolving time is 22 minutes and the stirring speed is 110 rap.
[0070] S3. The molten mixture mixed in step S2 is introduced into an extrusion film blowing machine, and hot melt extrusion blow molding is performed at the same time to obtain a biodegradable plastic product reinforcement material.
[0071] Example 3
[0072] The biodegradable plastic product reinforcement material comprises the following components, measured by weight: 70 parts of shell flame retardant polymer modified polylactic acid, 110 parts of dandelion-shaped flame retardant, 28 parts of starch, 3 parts of plasticizer, 6 parts of microcrystalline cellulose, 32 parts of polyhydroxybutyrate, 2 parts of antioxidant, and 6 parts of dispersant.
[0073] The preparation method of the above-mentioned shelled flame-retardant polymer modified polylactic acid is as follows: by weight: 60 parts of polylactic acid and 8 parts of shelled flame-retardant polymer are dried under vacuum conditions at 80°C for 14 hours to remove moisture, and mixed evenly by a melt mixing processing method. The temperature of the melt mixing processing method is 180°C, the rotation speed is 60rpm, and the mixing time is 12min to obtain shelled flame-retardant polymer modified polylactic acid.
[0074] The preparation method of the shelled flame-retardant polymer is as follows: by weight, 24 parts of ammonium polyphosphate are dissolved in 420 parts of deionized water, and then 3 parts of chitosan are dissolved in 40 parts of 10% acetic acid aqueous solution to form a chitosan solution for use, and 2 parts of alginate are dissolved in 37 parts of 1% ammonia aqueous solution to form an alginate solution. Then, the chitosan solution is added dropwise to the alginate solution and stirred for 9 minutes to generate the alginate solution, and then the shelled flame-retardant polymer is obtained after centrifugation, washing, and drying.
[0075] The dandelion-shaped flame retardant is composed of a spherical magnesium aluminum hydroxide flame retardant and melamine phosphate nanowires distributed in a scattered manner on its outer layer.
[0076] The average diameter of the spherical magnesium aluminum hydroxide flame retardant is 5 μm, and the average diameter of the melamine phosphate nanowire is 80 nm and the length is 1200 nm.
[0077] The mass ratio of the spherical magnesium aluminum hydroxide flame retardant to the melamine phosphate nanowire is 20:1.
[0078] The preparation method of the dandelion-shaped flame retardant is as follows: by weight, 22 parts of melamine are dissolved in 320 parts of dimethylformamide to form a solution A for standby use, and then 22 parts of polyphosphoric acid are dissolved in 140 parts of polyphosphoric acid in the same way to form a solution B, and then the solution A is dripped into the solution B completely over 4 hours, and after the dripping is completed, 60 parts of spherical magnesium aluminum hydroxide flame retardant are added, heated to 112°C, stirred for reaction for 9 hours, and melamine phosphate nanowires are uniformly grown on the surface of the spherical hydroxide inorganic flame retardant, and then the product is filtered and washed three times with deionized water, and then the product is dried at 70°C for 30 hours to obtain a dandelion-shaped flame retardant.
[0079] The preparation method of the spherical magnesium aluminum hydroxide flame retardant is as follows: by weight, 40 parts of Mg(NO3)2·6H2O and 20 parts of Al(NO3)3·9H2O are dissolved in 100 parts of deionized water to form a magnesium aluminum salt solution for use. A C alkaline solution is obtained by dissolving 12 parts of Na2CO3 and 27 parts of NaOH in 150 parts of deionized water. The magnesium aluminum salt solution is vigorously stirred, and the pH of the magnesium aluminum salt solution is maintained at 9 with the C alkaline solution during the stirring process. A hydroxide precipitate is formed during the stirring process, and then filtered and washed with deionized water to neutrality, and then vacuum dried to obtain a spherical magnesium aluminum hydroxide flame retardant.
[0080] The plasticizer mentioned above is epoxidized soybean oil.
[0081] The antioxidant mentioned above is sesamol.
[0082] The above-mentioned dispersant is polyvinyl alcohol.
[0083] The present invention also provides a method for preparing a biodegradable plastic product reinforcement material:
[0084] S1. melt-blending the shell flame-retardant polymer modified polylactic acid, dandelion-shaped flame retardant, dispersant and plasticizer at a heating temperature of 170° C. for 3 h.
[0085] S2. Then continue to add starch, microcrystalline cellulose, antioxidants and polyhydroxybutyrate and heat to dissolve at 130°C. The heating and dissolving time is 26 minutes and the stirring speed is 130 rap.
[0086] S3. The molten mixture mixed in step S2 is introduced into an extrusion film blowing machine, and hot melt extrusion blow molding is performed at the same time to obtain a biodegradable plastic product reinforcement material.
[0087] Example 4
[0088] The biodegradable plastic product reinforcement material comprises the following components, measured by weight: 80 parts of shell flame retardant polymer modified polylactic acid, 120 parts of dandelion-shaped flame retardant, 30 parts of starch, 4 parts of plasticizer, 7 parts of microcrystalline cellulose, 35 parts of polyhydroxybutyrate, 3 parts of antioxidant, and 7 parts of dispersant.
[0089] The preparation method of the above-mentioned shelled flame-retardant polymer modified polylactic acid is as follows: by weight: 60 parts of polylactic acid and 9 parts of shelled flame-retardant polymer are dried under vacuum conditions at 90°C for 16 hours to remove moisture, and mixed evenly by a melt mixing processing method. The temperature of the melt mixing processing method is 190°C, the rotation speed is 65rpm, and the mixing time is 15min to obtain the shelled flame-retardant polymer modified polylactic acid.
[0090] The preparation method of the shelled flame-retardant polymer is as follows: by weight, 28 parts of ammonium polyphosphate are dissolved in 450 parts of deionized water, and then 4 parts of chitosan are dissolved in 50 parts of 10% acetic acid aqueous solution to form a chitosan solution for standby use, and 3 parts of alginate are dissolved in 40 parts of 1% ammonia aqueous solution to form an alginate solution. Then, the chitosan solution is added dropwise to the alginate solution and stirred for 10 minutes to generate the alginate solution, and then the shelled flame-retardant polymer is obtained after centrifugation, washing, and drying.
[0091] The mass ratio of the above-mentioned shell flame-retardant polymer to polylactic acid is 9:60.
[0092] The dandelion-shaped flame retardant is composed of a spherical magnesium aluminum hydroxide flame retardant and melamine phosphate nanowires distributed in a scattered manner on its outer layer.
[0093] The average diameter of the spherical magnesium aluminum hydroxide flame retardant is 6 μm, and the average diameter of the melamine phosphate nanowire is 90 nm and the length is 1500 nm.
[0094] The mass ratio of the spherical magnesium aluminum hydroxide flame retardant to the melamine phosphate nanowire is 25:1.
[0095] The preparation method of the dandelion-shaped flame retardant is as follows: by weight, 25 parts of melamine are dissolved in 350 parts of dimethylformamide to form a solution A for standby use, and then 25 parts of polyphosphoric acid are dissolved in 150 parts of polyphosphoric acid in the same way to form a solution B, and then the solution A is completely dripped into the solution B in 5 hours, and after the dripping is completed, 65 parts of spherical magnesium aluminum hydroxide flame retardant are added, heated to 120°C, stirred for 12 hours, and melamine phosphate nanowires are uniformly grown on the surface of the spherical hydroxide inorganic flame retardant, and then the product is filtered and washed three times with deionized water, and then the product is dried at 80°C for 40 hours to obtain a dandelion-shaped flame retardant.
[0096] The preparation method of the spherical magnesium aluminum hydroxide flame retardant is as follows: by weight, 46 parts of Mg(NO3)2·6H2O and 23 parts of Al(NO3)3·9H2O are dissolved in 100 parts of deionized water to form a magnesium aluminum salt solution for use. A C alkaline solution is obtained by dissolving 15 parts of Na2CO3 and 20 parts of NaOH in 150 parts of deionized water. The magnesium aluminum salt solution is vigorously stirred, and the pH of the magnesium aluminum salt solution is maintained at 9 with the C alkaline solution during the stirring process. A hydroxide precipitate is formed during the stirring process, and then filtered and washed with deionized water to neutrality, and then vacuum dried to obtain a spherical magnesium aluminum hydroxide flame retardant.
[0097] The plasticizer mentioned above is n-butyl stearate.
[0098] The antioxidant mentioned above is sesamol.
[0099] The above-mentioned dispersant is polyvinyl alcohol.
[0100] The present invention also provides a method for preparing a biodegradable plastic product reinforcement material:
[0101] S1. melt-blending the shell flame-retardant polymer modified polylactic acid, dandelion-shaped flame retardant, dispersant and plasticizer at a heating temperature of 180° C. for 3 h.
[0102] S2. Then continue to add starch, microcrystalline cellulose, antioxidants and polyhydroxybutyrate and heat to dissolve at 140°C. The heating and dissolving time is 30 minutes and the stirring speed is 140rap.
[0103] S3. The molten mixture mixed in step S2 is introduced into an extrusion film blowing machine, and hot melt extrusion blow molding is performed at the same time to obtain a biodegradable plastic product reinforcement material.
[0104] Example 5
[0105] The method is basically the same as Example 1, except that the amount of polylactic acid modified by the shelling flame-retardant polymer added to the prepared biodegradable plastic product is 80 parts.
[0106] Example 6
[0107] The method is basically the same as Example 1, except that the amount of dandelion-like flame retardant added to the prepared biodegradable plastic product is 100 parts.
[0108] Comparative Example 1
[0109] It is basically the same as Example 1, except that the polylactic acid is not modified by the shell flame retardant polymer.
[0110] Comparative Example 2
[0111] The method is basically the same as Example 1, except that the dandelion-shaped flame retardant is replaced by a spherical magnesium aluminum hydroxide flame retardant, so the flame retardant does not contain the melamine phosphate nanowires with scattered distribution on the outer layer of the surface.
[0112] Comparative Example 3
[0113] It is basically the same as Example 1, except that the dandelion-shaped flame retardant is replaced by melamine phosphate nanowires, so the flame retardant does not contain the spherical magnesium aluminum hydroxide flame retardant on the surface.
[0114] Comparative Example 4
[0115] It is basically the same as Example 1, except that the spherical magnesium aluminum hydroxide flame retardant and the melamine phosphate nanowires are added separately and do not form a coating relationship.
[0116] Fourier transform infrared spectroscopy (FTIR) was used to test the flame retardant polymer modified polylactic acid in the shell under attenuated total reflectance (ATR) mode. All spectra were recorded in the range from 4000 to 400 cm -1 , the spectral resolution is 4cm -1 , the number of scans is 32 times.
[0117] Figure 1 The infrared Fourier transform infrared (FTIR) spectrum of the polylactic acid modified with the shelled flame retardant polymer prepared in Example 1 of the present invention shows that since the hydrogen bond weakens the force constant of the C=O bond, the formation of the hydrogen bond on the carbon group can cause the C=O asymmetric stretching mode of the ester in the polylactic acid segment to undergo a red shift, so the carbonyl absorption peak of the polylactic acid modified with the shelled flame retardant polymer changes from 1755 cm -1 Move to 1752cm -1 ,The above results prove that there may be hydrogen bonding interactions between PLA and the core-shell flame retardant.
[0118] The present invention uses a scanning electron microscope, spherical magnesium aluminum hydroxide and dandelion-shaped flame retardant to observe the morphology. Figure 2 This is a scanning electron microscope (SEM) morphology picture of the spherical magnesium aluminum hydroxide prepared in Example 1 of the present invention. It can be seen from the table that the magnesium aluminum hydroxide is obviously spherical. Figure 3 This is a scanning electron microscope (SEM) morphology image of the dandelion-shaped flame retardant prepared in Example 1 of the present invention. It can be seen that the flame retardant presents an obvious dandelion shape.
[0119] X-ray diffraction (XRD) was used to characterize the phases of spherical magnesium aluminum hydroxide and dandelion-shaped flame retardant. Figure 4 This is the phase analysis diagram of spherical magnesium aluminum hydroxide. From the figure, we can see obvious diffraction peaks of magnesium hydroxide and aluminum hydroxide, which proves the effectiveness of the phase. Figure 5 It is a dandelion-shaped flame retardant phase. In addition to the diffraction peaks of magnesium hydroxide and aluminum hydroxide, there is also a diffraction peak of melamine phosphate, which proves that the surface of the spherical magnesium aluminum hydroxide contains a melamine phosphate phase.
[0120] Performance Test:
[0121] Mechanical properties: The tensile properties of the material comply with GB / T1040 "Determination of tensile properties of plastics"; the impact strength is tested with reference to GB / T 1843-1996 "Plastic cantilever beam impact test method".
[0122] Flame retardant performance: Flame retardant performance testing is a key link in evaluating the safety and fire resistance of materials under fire conditions. This test is usually conducted in accordance with the UL 94 fire test standard. In the UL 94 test, the sample is placed on a specific combustion device, and its combustion behavior is ignited and observed, including parameters such as burning time, burning speed, flame spread, and smoke and harmful gases produced after combustion, so as to comprehensively evaluate the flame retardant performance of the material. These test data provide an important basis for evaluating the performance of materials under fire conditions, and are used to judge the safety and fire resistance of materials, ensuring that they can slow down the spread of fire and reduce potential hazards when a fire occurs.
[0123] Table 2 Performance test results of materials of Examples 1 to 6 and Comparative Examples 1 to 4
[0124]
[0125] The main difference between Comparative Example 1 and Example 1 is whether the polylactic acid is modified with a shell-encapsulated flame-retardant polymer. From Table 2, it can be seen that the shell-encapsulated flame-retardant polymer modification can significantly improve the mechanical properties and flame retardant properties of the biodegradable plastic product.
[0126] The main difference between Comparative Example 2 and Example 1 is whether the spherical magnesium aluminum hydroxide contains melamine phosphate nanowires. It can be seen from Table 2 that melamine phosphate nanowires can significantly improve the mechanical properties and flame retardant properties of biodegradable plastic products.
[0127] The main difference between Comparative Example 3 and Example 1 is whether the coating contains a spherical magnesium aluminum hydroxide flame retardant. It can be seen from Table 2 that the spherical magnesium aluminum hydroxide flame retardant can significantly improve the mechanical properties and flame retardant properties of the biodegradable plastic product.
[0128] The main difference between Comparative Example 4 and Example 1 is whether the spherical magnesium aluminum hydroxide flame retardant and the melamine phosphate nanowires are in a coating relationship. It can be seen from Table 2 that the coating relationship between the spherical magnesium aluminum hydroxide flame retardant and the melamine phosphate nanowires can significantly improve the mechanical properties and flame retardant properties of biodegradable plastic products.
[0129] The core-shell flame-retardant polymer and dandelion-shaped flame retardant of the present invention have excellent flame retardancy, mechanical properties and environmentally friendly degradation characteristics. Therefore, the biodegradable plastic product reinforcement material of the present invention has excellent mechanical properties and flame retardancy and has wide application value.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. Biodegradable plastic product reinforcement material, characterized in that: The composition comprises the following components in parts by weight: 45-80 parts of shell flame retardant polymer modified polylactic acid, 80-120 parts of dandelion-shaped flame retardant, 20-30 parts of starch, 2-4 parts of plasticizer, 3-7 parts of microcrystalline cellulose, 20-35 parts of polyhydroxybutyrate, 1-3 parts of antioxidant, and 3-7 parts of dispersant; The preparation method of the shelled flame-retardant polymer modified polylactic acid is as follows: by weight: 60 parts of polylactic acid and 3-9 parts of shelled flame-retardant polymer are dried under vacuum conditions at 70-90° C. for 8-16 hours, and mixed evenly by a melt mixing process, wherein the temperature of the melt mixing process is 140-190° C., the rotation speed is 45-65 rpm, and the mixing time is 8-15 minutes, to obtain the shelled flame-retardant polymer modified polylactic acid; The preparation method of the dandelion-shaped flame retardant is as follows: by weight, 15 to 25 parts of melamine are dissolved in 200 to 350 parts of dimethylformamide to form a solution A for standby use, and then 15 to 25 parts of polyphosphoric acid are dissolved in 100 to 150 parts of polyphosphoric acid in the same way to form a solution B, and then the solution A is completely dripped into the solution B in the form of dripping within 3 to 5 hours, and after the dripping is completed, 30 to 65 parts of spherical magnesium aluminum hydroxide flame retardant is added, heated to 100 to 120° C., stirred for reaction for 6 to 12 hours, and melamine phosphate nanowires are uniformly grown on the surface of the spherical hydroxide inorganic flame retardant, and then the product is filtered and washed with deionized water, and then the product is dried at 60 to 80° C. for 20 to 40 hours to obtain the dandelion-shaped flame retardant; The preparation method of the spherical magnesium aluminum hydroxide flame retardant is as follows: by weight, 24 to 46 parts of Mg(NO3)2·6H2O and 12 to 23 parts of Al(NO3)3·9H2O are dissolved in 100 parts of deionized water to form a magnesium aluminum salt solution for standby use; 10 to 15 parts of Na2CO3 and 12 to 20 parts of NaOH are dissolved in 150 parts of deionized water to obtain a C alkaline solution; the magnesium aluminum salt solution is vigorously stirred, and the pH value of the magnesium aluminum salt solution is kept at 8 to 9 with the C alkaline solution during the stirring process, a hydroxide precipitate is formed during the stirring process, and then it is filtered and washed with deionized water to neutrality, and then vacuum dried to obtain the spherical magnesium aluminum hydroxide flame retardant; The preparation method of the shelled flame-retardant polymer is as follows: by weight, 15 to 28 parts of ammonium polyphosphate are dissolved in 350 to 450 parts of deionized water, and then 1 to 4 parts of chitosan are added and dissolved in 30 to 50 parts of 10% by weight acetic acid aqueous solution to form a chitosan solution for standby use, and 1 to 3 parts of alginate are dissolved in 30 to 40 parts of 1% by weight ammonia aqueous solution to form an alginate solution; then, the chitosan solution is added dropwise to the alginate solution and stirred for 5 to 10 minutes to generate the alginate solution, and then the shelled flame-retardant polymer is obtained after centrifugation, washing and drying.
2. The biodegradable plastic product reinforcing material according to claim 1, characterized in that: The dandelion-shaped flame retardant consists of a spherical magnesium aluminum hydroxide flame retardant and melamine phosphate nanowires distributed in a scattered manner on its outer layer.
3. The biodegradable plastic product reinforcement material according to any one of claims 1 or 2, characterized in that: The average diameter of the spherical magnesium aluminum hydroxide flame retardant is 2-6 μm, and the average diameter of the melamine phosphate nanowire is 40-90 nm, and the length is 500-1500 nm.
4. The biodegradable plastic product reinforcement material according to claim 3, characterized in that: The mass ratio of the spherical magnesium aluminum hydroxide flame retardant to the melamine phosphate nanowire is (10-25):
1.
5. The biodegradable plastic product reinforcing material according to claim 1, characterized in that: The mass ratio of melamine to polyphosphoric acid is 1:
1.
6. The biodegradable plastic product reinforcing material according to claim 1, characterized in that: The mass ratio of Mg(NO3)2·6H2O to Al(NO3)3·9H2O is 2:
1.
7. The biodegradable plastic product reinforcing material according to claim 1, characterized in that: The plasticizer is hydrogenated castor oil, n-butyl stearate or epoxidized soybean oil; The antioxidant is lycopene or sesamol; The dispersant is polyvinyl alcohol or sodium carboxymethyl cellulose.
8. The method for preparing a biodegradable plastic product reinforcement material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. melt-blending the shell flame-retardant polymer modified polylactic acid, dandelion-shaped flame retardant, dispersant and plasticizer at a heating temperature of 150-180° C. for 2-3 h; S2. Then continue to add starch, microcrystalline cellulose, antioxidant and polyhydroxybutyrate and heat to dissolve at 100-140°C for 20-30 minutes at a stirring speed of 100-140 rpm; S3. The molten mixture mixed in step S2 is introduced into an extrusion film blowing machine, and hot melt extrusion blow molding is performed at the same time to obtain a biodegradable plastic product reinforcement material.
Citation Information
Patent Citations
Degradable plastic and preparation method thereof
CN116948266A
Degradable flame-retardant plastic film
CN117844210A
Polyhydroxylkanoates as well as blending modification for copolymer thereof and polylactic acid
CN101205356A
Environment-friendly plastic flame retardant, preparation method and application of environment-friendly plastic flame retardant in plastic
CN111518316A